Penerapan Sistem Pendidikan Islam: Kajian tentang Strategi, Sumber Daya, dan Mutu - Rhoni Rodin; Endang Endang; Murni Yanto; Muhammad Istan; Beni Azwar (An-Nahdloh: Journal of Education and Islamic Studies, 2025)
The Islamic education system plays a strategic role in shaping a generation that is not only intellectually competent but also spiritually and morally grounded. This article examines the implementation of Islamic education by focusing on three key aspects: strategic planning, resource management, and quality assurance. The study is motivated by the urgent need for Islamic education to respond to contemporary challenges, particularly in an era marked by globalization and digital transformation, which demand an education system that is both relevant and competitive. This research employs a qualitative approach through a comprehensive literature review of policy documents, scholarly sources, and field practices observed in various Islamic educational institutions. The findings reveal that effective implementation strategies must be grounded in a clear vision and mission, well-developed strategic planning, and strong, visionary leadership. Efficient management of resources—particularly qualified educators, infrastructure, and funding—significantly contributes to the success of the learning process. Moreover, an integrated and continuous quality assurance system is crucial for maintaining educational standards and ensuring institutional accountability. In today’s context, the integration of Islamic values with modern management practices, adopting information technology, is vital in advancing a high-quality, adaptive, and globally competitive Islamic education system. This study recommends fostering stronger collaboration among the government, educational institutions, and society to establish a holistic and sustainable framework for Islamic education. Keywords: Islamic education, implementation strategy, educational resources, education quality, Islamic education management